Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1968
DOI: 10.1002/pen.760080302
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of mechanical properties on molecular motion in polymers

Abstract: Considerable progress has been made in the past 20 years in the synthesis, characterization and fabrication of plastics. Previous SPE Award winners, such as Mark, Natta, and Marvel dealt largely with synthesis; Flory with characterization; Alfrey and Du Bois with fabrication. One of the still unsolved problems lies in the realm of relating mechanical properties, such as impact strenght and creep to molecular structure. The design enginner who wishes to use a plastic part is concerned primarily with how some pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
174
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 368 publications
(193 citation statements)
references
References 61 publications
15
174
0
4
Order By: Relevance
“…Os estudos que buscam correlacionar o comportamento dinâmi-co-mecânico e a resistência ao impacto tiveram início por volta de 1950 41 . A questão a ser considerada era se havia correlação entre as propriedades mecânicas de polímeros e o comportamento dinâmico-mecânico na região de temperatura de solicitação do material que, em geral, para polímeros vítreos está abaixo da temperatura de transição vítrea.…”
Section: Correlação Entre a Curva De "Damping" E As Propriedades Mecâunclassified
See 2 more Smart Citations
“…Os estudos que buscam correlacionar o comportamento dinâmi-co-mecânico e a resistência ao impacto tiveram início por volta de 1950 41 . A questão a ser considerada era se havia correlação entre as propriedades mecânicas de polímeros e o comportamento dinâmico-mecânico na região de temperatura de solicitação do material que, em geral, para polímeros vítreos está abaixo da temperatura de transição vítrea.…”
Section: Correlação Entre a Curva De "Damping" E As Propriedades Mecâunclassified
“…41) acreditavam que a existência de uma relaxação secundária abaixo da temperatura de transição vítrea poderia ser a responsável pela tenacidade encontrada em alguns polímeros, tomando como principais exemplos para isto o policarbonato (PC) e o poliestireno de alto impacto (HIPS). Nestes dois materiais há a ocorrência de uma relaxação à baixa temperatura, sendo o caso do PC já citado, enquanto que no HIPS essa relaxação é relacionada à transição ví-trea da fase borracha e sua temperatura pode variar de -100 a -20 o C, dependendo principalmente do tipo da borracha utilizada.…”
Section: Correlação Entre a Curva De "Damping" E As Propriedades Mecâunclassified
See 1 more Smart Citation
“…In addition to the primary (a-) relaxations that are responsible for the viscous flow, a kind of secondary relaxation, called Johari-Goldstein or b-relaxation [7][8][9] , often exists at high frequencies or low temperatures. Recent studies have demonstrated that b-relaxations are an intrinsic and universal feature of supercooled liquids and glasses 1,8,10 , and they are of significance to the understanding of many key issues in glassy physics and material sciences 1 , ranging from glass transition phenomenon [10][11][12][13] , diffusions [14][15][16][17] , physical aging 18,19 to mechanical properties 20,21 and mechanisms of plastic deformations [21][22][23] , as well as the stabilities and crystallization of glassy materials [24][25][26] .…”
mentioning
confidence: 99%
“…On the other hand, to understand the dominating factors that govern the behaviours of b-relaxation are of practical importance. For example, polymers and MGs with pronounced b-relaxations at relatively low temperatures (for example, below or near room temperature) usually exhibit good ductility and they are favoured for mechanical applications 20,21 . However, for the pharmaceuticals industry, b-relaxations are sometimes undesired and should be suppressed as they cause the devitrification and destabilization of glassy medicines, which have better solubility and bioavailability than their crystalline counterparts 1,10,24,25 .…”
mentioning
confidence: 99%